P199 Terminal ileum ileoscopy and histology in patients undergoing high-definition colonoscopy with virtual chromoendoscopy for chronic non-bloody diarrhoea: a prospective, multi-centre study. (25th January 2019) - Borsotti, E; Barberio, B; D'Incà, R; Bonitta, G; Cavallaro, F; Pastorelli, L; Rondonotti, E; Samperi, L; Neumann, H; Viganò, C; Vecchi, M; Tontini, E
Abstract: Background: Ileocolonoscopy is the procedure of choice for chronic non-bloody diarrhoea (CNBD) of unknown origin. The histological evaluation at different colonic sites is mandatory to assess the presence of microscopic colitis. However, the value of routine ileal biopsies upon normal appearing mucosa as assessed by means of standard resolution white-light ileoscopy is controversial given its reported low diagnostic yield. Hence, we assessed, for the first time, the accuracy of retrograde ileoscopy using high-definition and dye-less chromoendoscopy (HD+DLC), thereby calculating the impact and cost of routine ileal biopsies in CNBD. Methods: Patients with CNBD of unknown origin were prospectively enrolled for ileocolonoscopy with HD+DLC in five referral centres. Multiple biopsies were systematically performed in each colo-rectal segment and in the terminal ileum for histopathological analyses. Results: Between 2014 and 2017, 546 consecutive patients were recruited. Retrograde ileoscopy success rate was 97.6%. In total, 492 patients (mean age 53 ± 18 years) fulfilled all inclusion criteria: following endoscopic and histopathological work-up, Abstract P199 Diagnostic definition based on ileocolorectal endoscopy and histo-patholology in patients with chronic non-bloody diarrhoea of unknown origin. LNH, lymphoid nodular hyperplasia; NSAIDs, non-steroidal anti-inflammatory drugs. Seven per cent had lymphoid nodular hyperplasia and 3% had isolated ileitis. Abstract P199 Terminal ileum endoscopic and histo-pathological assessment in patients with chronic non-bloody diarrhoea of unknown origin. LNH, lymphoid nodular hyperplasia; NSAIDs, non-steroidal anti-inflammatory drugs. Compared with the histopathology gold standard, retrograde ileoscopy with HD+DLC showed 93% sensitivity, 98% specificity, and 99.8% negative predictive value. Statistical measures of the performance of retrograde ileoscopy with high-definition plus virtual chromo-endoscopy performance using histopathology as the gold standard. In patients with normal ileocolonoscopy, ileum histology had no diagnostic gain and a $26.5 cost per patient. Conclusions: Retrograde ileoscopy with HD+DLC predicts with excellent performance the presence of ileitis in CNBD. The histopathological evaluation of the terminal ileum is the gold standard for the diagnostic assessment of visible lesions but has no added diagnostic value in CNBD patients with negative ileo-colonoscopy inspection using modern endoscopic imaging techniques.